Neurological and cognitive disorders after coronary artery bypass grafting. - Taggart, D; Westaby, S (2001)
Cerebral injury is a major cause of mortality and morbidity of coronary artery bypass grafting. Stroke occurs in 3% of patients and is largely caused by embolization of atheromatous debris during manipulation of the diseased aorta. Cognitive impairment, which is predominantly caused by microembolization of gaseous and particulate matter, mainly generated by cardiotomy suction, is more common. Demonstration of similar cognitive impairment in patients operated on without cardiopulmonary bypass indicates that other pathophysiological mechanisms, such as anaesthesia and hypoperfusion, are also involved. Advances in medical, anesthetic, and surgical management have resulted in a reduction in the incidence of neurological injury in CABG patients over the past decade. On the other hand, an increasingly elderly population with more severe comorbidity, who are more prone to cerebral injury, are increasingly being referred for CABG. Possible mechanisms to reduce overt and subtle cerebral injury are discussed. The use of composite arterial grafts performed on the beating heart may be the most effective way of minimizing the risk of cerebral injury associated with CABG.